PENGGUNAAN MULTIMEDIA INTERAKTIF PADA PEMBELAJARAN BAHASA INGGRIS TERHADAP HASIL BELAJAR SPEAKING DI SMPN 37 JAKARTA - Rusmi Rusmi; Zulfitria Zulfitria (Media Riset Bisnis Manajemen Akuntansi, 2026)
This study aims to analyze in depth how the use of interactive multimedia in English language learning affects students' speaking skills at SMPN 37 Jakarta. The background of the study stems from the low speaking proficiency among students, which is partly due to the lack of engaging and interactive learning media. Through the use of digital learning applications and multimedia content, it is expected that students will become more motivated, active, and involved in the learning process.This research employs a descriptive qualitative approach, with data collected through classroom observations, in-depth interviews with teachers and students, as well as documentation of the teaching and learning process in Grade VII. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing.The findings indicate that the use of interactive multimedia has a positive impact on student engagement in English language learning. Students appeared more confident, enthusiastic, and capable of expressing themselves orally in English. Additionally, teachers found interactive media helpful in facilitating more varied and enjoyable instruction. These findings suggest that interactive multimedia not only contributes to improved learning outcomes but also fosters more meaningful learning experiences for students.Keywords: Interactive Multimedia, English Language Learning, Speaking Skills, Qualitative Study, Junior High School